The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1063/1.4868586
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-driven precipitate growth and ripening of oxygen precipitates in boron doped silicon by dynamical x-ray diffraction

Abstract: X-ray Pendellösung fringes from three silicon single crystals measured at 900 °C are analyzed with respect to density and size of oxygen precipitates within a diffusion-driven growth model and compared with TEM investigations. It appears that boron doped (p+) material shows a higher precipitate density and a higher strain than moderately (p-) boron crystals. In-situ diffraction reveals a diffusion-driven precipitate growth followed by a second growth regime in both materials. An interpretation of the second gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
3
9
0
Order By: Relevance
“…As shown previously in Ref. 21, this yield within the model of spherical precipitates a higher linear misfit strain e in the p þ sample as compared to pÀ material.…”
supporting
confidence: 86%
See 3 more Smart Citations
“…As shown previously in Ref. 21, this yield within the model of spherical precipitates a higher linear misfit strain e in the p þ sample as compared to pÀ material.…”
supporting
confidence: 86%
“…The feature that pþ samples show a higher e and thus higher aspect ratio holds for all specimens presented here and in Ref. 21. Even though the difference in e in the sample set without nucleation step at 450 C is quite small.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…29 It also is in contradiction to the effective constrained misfit of platelets determined in a previous work where e plate was found to be 0.193 by evaluating thickness dependent Pendell€ osung oscillations in combination with TEM data 7 and to the results of a more recent work 30 utilizing the same technique where it was found that the higher the aspect ratio the lower e plate . Therefore, it has to be questioned if the precipitate population in these two samples is sufficiently characterized and respected in the evaluation.…”
Section: Discussionmentioning
confidence: 58%